Imaging techniques in breast cancer. Issue 1 (January 2016) - Redman, Alan; Lowes, Simon; Leaver, Alice
Abstract: Imaging plays a critical role in the diagnosis and management of breast cancer. Two-view mammography and ultrasound form the mainstay of breast imaging and are essential components of the triple assessment. Digital mammography is rapidly replacing analogue mammography, and recent advances such as digital tomosynthesis add a third dimension to conventional 2D mammographic images. The versatility of ultrasound allows assessment of the breast and axilla as well as accurately targeted interventions, from the simple diagnostic core biopsy to preoperative tumour localization. It also guides large volume biopsies and excision of certain benign lesions, which in some cases can obviate surgical excision. Newer ultrasound techniques being applied to the breast and axilla include elastography and the use of intradermal microbubbles to guide the radiologist to the sentinel axillary node. Breast MRI is a powerful modality in assessing breast cancer. It can provide accurate information on size and multifocality of lesions, particularly those that are mammographically challenging such as lobular cancers, and it is also used to assess response to neoadjuvant chemotherapy and guide surgical management. CT scans, and in selected cases Positron Emission Tomography, play important roles in the assessment of metastatic disease.